Nyadar: Religious and Cultural Resistance of Madurese Salt Farming Community - Dzulkarnain, Iskandar; Soetarto, Endriatmo; A Kinseng, Rilus; Sjaf, Sofyan (Sodality: Jurnal Sosiologi Pedesaan, 2020)
This article discusses the issues of religious and cultural resistance of Madurese salt farming communities as portrayed in the religious tradition of nyadar ritual. Nyadar is an annual religious tradition carried out by Madurese salt farming communities in Sumenep district, precisely in Pinggir Papas Village, Kalianget District and Gersik Putih Village, Gapura District, to conduct cultural resistance against the hegemony and dominance of the Salt Farming Corporation and Madurese salt farming community elites. The purpose of this study is to reveal changes in the cultural situation of the Madurese salt farming community. This study uses an ethnographic method with a constructivist paradigm with data collection methods using in-depth interviews, participant observation, and focus group discussions (FGD). The result of this research found that nyadar is a form of religious rituals that illustrates the solidarity of the community in fighting against the shackles of poverty and helplessness to fight the hegemony and domination of the economic liberalism capitalism in the globalization of the global salt economy which tends to favor the salt corporation, the owners of salt farm land, the religious figures, and the Madurese elites. The cultural resistance of the salt farming community is portrayed in the rejection of the various policies that will be enforced by the Government, PT. Garam, as well as salt corporates in the religious ritual tradition of nyadar including in determining the time of event, religious tourism destinations, and financial support to celebrate the religious ritual activities of nyadar.